Living city as a criterion of social and ecological sustainability of urban space - Shushunova, Tatyana N. (Journal of the Belarusian State University. Ecology, 2020)
The results of a qualitative sociological study using the methods of visual sociology carried out as part of a naturalistic paradigm for the study of an amusement park of a small city in order to identify its attractiveness for people of different ages are presented. Currently, city parks are faced with the challenges of modern times, requiring them to revise the values that they are called to broadcast; modernization of the existing infrastructure inherited from the Soviet era, revision of the structure of leisure, educational and cultural interests, which should be consistent with the preferences of citizens. The concept of a «living city» is considered.
Keywords: architectonics of the urban environment; visual sociology; vibrant city; open urban space; recreational activities; social sustainability of the city